Stable conductive polymer in liquid media for continuous monitoring - Benoudjit, Abdel Mohsen; Shalihah Shohibuddin, Ihda Uswatun; Wan Salim, Wan Wardatul Amani (2019)
There is an urgency to establish an early warning system in Malaysia to predict contamination in water quality (toxic pollution at Sungai Kim Kim in Johor). • Continuous water-quality monitoring is key to establish an early warning system so remedial actions can be taken effectively by government, industries, and local communities. • Electrochemical sensor technology could be used for continuous monitoring (low cost of the fabrication process, sample to operate and scalable) PEDOT:PSS are not without any limitations; the presence of PSS acting as a dopant to stabilize PEDOT:PSS results in PEDOT:PSS being highly hydrophilic and having an appreciable degree of water solubility which in turn leads to PEDOT:PSS film degeneration and peeling off easily from the surface of electrodes, while at the same time affecting its use in aqueous media for continuous monitoring.